Aus der Arbeit der Bibliothek des ehemaligen Deutschen Entomologischen Institutes: Nachlaß Kraatz, Berlin. - Marwinski, Felicitas (Contributions to Entomology = Beiträge zur Entomologie, 1975)
The papers left by the coleopterologist and systematist Professor Gustav Kraatz and preserved in the library of the former Deutsches Entomologisches Institut were filed. They consist of 17.901 letters and post-cards from 984 correspondents covering the years from 1845 bis 1908 and of some documents.